Understanding the dynamics of friendship formation among high school adolescent: Indigenous psychology approach - Banyu Wicaksono; Maria Goretti Adiyanti (Department of Psychology, Universitas Negeri Yogyakarta, 2019)
How friendship between adolescent peers was formed is yet to be understood clearly. Whereas number of studies has clearly linked quality of friendship to various adaptive ability, school performance, and academic achievements. This study attempted to understand the dynamics of friendship formation in sample Javanese adolescents using indigenous psychology as its’ paradigm. Data was obtained from 120 respondents, (82 Girls, and 38 Boys) using open-ended questionnaire, which asks about how friendship between the respondent and their best friend(s) was formed. Data was analyzed using thematic analysis to identify themes and subthemes that indicates how friendship was formed. The result showed that there are two major theme that emerges in the beginning of friendship formation followed by other qualities related to it. This study reveals one more important aspect to be considered in understanding friendship formation between adolescents and their close friends